Análisis de biopsias gástricas endoscópicas en caninos (2007)
ABSTRACT: This article presents the histopathological findings in 410 endoscopic gastric biopsies obtained from different gastric areas in 98 dogs with digestive related symptoms, and from 20 asymptomatic dogs. Biopsies were obtained by gastroscopies performed in a veterinary clinic in the city of Medellin (Colombia), between January 2002 and June 2006. The histopathological specimens collected along this period were reevaluated searching specifically for the presence of gastritis and Helicobacter spp., and the results were related with age, breed, sex and the owner’s social status. Helicobacter spp. was found in 46% of the animals (55% asymptomatic and 43.8% asymptomatic). Chronic gastritis was present in 51.2% of the animals (54% symptomatic and 70% asymptomatic). No statistical relationship was found between the presence of Helicobacter spp. and digestive symptoms, nor with age, breed, sex or social status (p>0.05); neither was there statistical association between chronic gastritis and the other variables analyzed. There were a strong statistical association between the presence of Helicobacter spp. and chronic gastritis (p<0.01). All dogs were sampled in fundic, corporal and antral gastric regions and it was found that Helicobacter spp. was more frequent in the corpus. Other occasional findings included gastric adenocarcinoma, benign ulcers and intestinal metaplasia.